ON THE QUESTION OF THE OPTIMAL AGE FOR STARTING SPORTS: RESULTS OF A BIBLIOMETRIC ANALYSIS OF THE WORKS OF FOREIGN AND RUSSIAN SCIENTISTS - Novikova, I.I.; Usacheva, E.V.; Zubtsovskaya, N.A.; Semenikhina, M.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the degree of elaboration of the issue of determining the optimal age for starting sports on the basis of a bibliometric analysis of the works of foreign and Russian scientists. Methods and structure of the study. Scientific work was carried out in three stages: 1) identification of the main areas of research on this issue using the PubMed database; 2) construction of a complex of top phrases (the most common) in the selected areas of research; 3) analysis of the works of domestic scientists using the scientific electronic library eLIBRARY.RU according to the selected top phrases. Publications for the period 2018-2022 were analyzed. Used library bibliometrix R-package. The study sample included 167 scientific publications on the topic under study. Results and conclusions. In the course of the analysis, three main areas of research on this issue were identified. Within the framework of the first direction, physiometric, anthropometric and other indicators characterizing the physical development of young athletes are analyzed, the second one examines the effect of physical activity on young basketball players, including the risk of their health disorders and injuries. The studies of the third direction are aimed at studying the factors similar to the second direction of young athletes in another sport - baseball. Based on a bibliographic search, it was determined that this issue is relevant in modern science and requires additional research to determine the optimal age for starting sports.